2009
DOI: 10.1111/j.1749-6632.2009.03699.x
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin as a Possible Lead Compound against Hormone‐Independent, Multidrug‐Resistant Breast Cancer

Abstract: We examine the possible evidence that the phytochemical curcumin may overcome resistance to hormonal and cytotoxic agents in breast cancer. We present our observations on MCF-7R, a multidrug-resistant (MDR) variant of the MCF-7 breast cancer cell line. In contrast to MCF-7, MCF-7R lacks aromatase and estrogen receptor alpha (ERalpha) and overexpresses the multidrug transporter ABCB1 and the products of different genes implicated in cell proliferation and survival, like c-IAP-1, NAIP, survivin, and COX-2. Never… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 22 publications
1
35
0
Order By: Relevance
“…Furthermore, it has been recently shown that curcumin induces immuno-restoration in tumour-bearing animals [5], indicating that the inclusion of this natural product in therapeutic regimens against cancer should be beneficial for great proportion of cancer patients, including those afflicted with breast carcinoma. Indeed, several publications have reported the anti-carcinogenic activity of curcumin against various breast cancer cell lines, including the multidrug-resistant ones [6][7][8]. Furthermore, numerous in vivo studies have shown its chemo-preventive effect against breast cancer [9].…”
Section: Introductionmentioning
confidence: 98%
“…Furthermore, it has been recently shown that curcumin induces immuno-restoration in tumour-bearing animals [5], indicating that the inclusion of this natural product in therapeutic regimens against cancer should be beneficial for great proportion of cancer patients, including those afflicted with breast carcinoma. Indeed, several publications have reported the anti-carcinogenic activity of curcumin against various breast cancer cell lines, including the multidrug-resistant ones [6][7][8]. Furthermore, numerous in vivo studies have shown its chemo-preventive effect against breast cancer [9].…”
Section: Introductionmentioning
confidence: 98%
“…The drugs that could be efficient against chemoresistant cells could be of great importance in enhancing effectiveness of cancer treatment. There are some data in the literature that verified anticancer properties of curcumin in drug resistant cells (Labbozzetta et al, 2009;Lu et al, 2012;Sung et al, 2009;Weir et al, 2007). However, these data should be more abundant in order to make more general conclusions about curcumin's activity against drug resistant cells.…”
Section: Discussionmentioning
confidence: 99%
“…This was shown for multidrug resistant myeloid leukemia cells (Lu et al, 2012), cisplatin resistant ovarian cancer cells (Weir et al, 2007), multiple myeloma cells resistant to 4 4 dexamethasone, doxorubicin and melphalan (Sung et al, 2009), as well as hormone independent, multidrug resistant breast cancer cells (Labbozzetta et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Recently, Curcumin analogs such as pyrazole and isoxazole 28 (Scheme 1 ) has been synthesized and evaluated for their anticancer activity. Both the analogs were found to possess enhanced anti-tumor potency against MCF-7 and MDR-transfected MCF-7 breast cancer cells [71, 72]. Furthermore, they reduced the expression levels of Bcl-2, Bcl-X L , and COX-2 in the breast cancer cells.…”
Section: Structural Analogs Of Curcuminmentioning
confidence: 99%
“…Furthermore, they reduced the expression levels of Bcl-2, Bcl-X L , and COX-2 in the breast cancer cells. These results suggest that these analogs could be effective anticancer agents for the treatment of hormone-independent MDR breast cancer [72]. In another report, electron-rich pyrazole and isoxazole analogs were synthesized and evaluated against two hormone-dependent and independent breast cancer cell lines [71].…”
Section: Structural Analogs Of Curcuminmentioning
confidence: 99%